25. Attentional dysfunctions in Ataxia-teleangectasia: A psychophysiological study. Issue 12 (December 2016) - Mannarelli, D.; Pauletti, C.; Leuzzi, V.; D'Agnano, D.; Rinalduzzi, S.; Currà, A.; Locuratolo, N.; Fattapposta, F.
Abstract : Ataxia-telangiectasia (AT) is a human disease caused by mutations in the ATM gene. The neural phenotype of AT includes progressive cerebellar neurodegeneration, which results in ataxia, oculocutaneous teleangiectasias, immunodeficiency, recurrent infections and proneness to cancer. Cognitive disturbances seem to affect both the attention and the executive functions. The aim of this study was to investigate the attentional functioning in AT patients using a psychophysiological evaluation. Ten young AT-patients (age: 12.4 ± 1.7 years) and ten matched healthy controls underwent a Contingent Negative Variation (CNV) recording. MICARS and UPDRS III scales were administered in order to assess clinical performance and disability. CNV amplitude (total and in two different temporal windows – W1, W2) was evaluated. Reaction times were also obtained. Total CNV amplitude (Fz p  = 0.001; Cz p  = 0.007; Pz p  = 0.03) and W2-CNV areas (Fz p  = 0.02; Pz p  = 0.05) were significantly lower in patients than in controls. RTs were prolonged in patients with respect to controls ( p  = 0.004). Our data indicated a difficulty in sustain attention and in motor preparation during an executive choice motor task. These attentional dysfunctions could result from the abnormal prefrontal-cerebellum circuit activity pattern, which has been proven to be altered in AT patients.